D-π-A chromophores with a quinoxaline core in the π-bridge and bulky aryl groups in the acceptor: Synthesis, properties, and femtosecond nonlinear optical activity of the chromophore/PMMA guest-host materials. (January 2021) - Kalinin, Alexey A.; Islamova, Liliya N.; Shmelev, Artemiy G.; Fazleeva, Guzel M.; Fominykh, Olga D.; Dudkina, Yulia B.; Vakhonina, Tatyana A.; Levitskaya, Alina I.; Sharipova, Anastasiya V.; Mukhtarov, Anvar S.; Khamatgalimov, Ayrat R.; Nizameev, Irek R.; et al.
Abstract: Novel D-π-A chromophores with quinoxaline/quinoxalinone core in the π-conjugated bridge and various bulky groups in the acceptor moiety have been synthesized and systematically investigated at molecular level by UV–Vis spectroscopy, DFT calculations, electrochemical and TGA-DSC methods as well as at materials level by the example of PMMA-based composite polymer materials doped with different chromophore contents using molecular modeling and SHG technique. Chromophores exhibit positive dioxane/chloroform solvatochromic shift of ca. 50 nm, high values of first hyperpolarizability and dipole moment, small energy gap and good thermal stability. Tolyl and cyclohexylphenyl substituents unlike phenyl can be treated as most effective isolating groups, preventing chromophore pronounced aggregation even at 30 wt% content. Femtosecond nonlinear optical (NLO) activity was studied for poled thin guest-host polymer films with various chromophore weight content. Film DBA-VQ Ph V-TCF PhCy (25 wt%)/PMMA with bulky cyclohexylphenyl groups in chromophore acceptor shows maximal NLO coefficient, d 33, values among the studied materials (37 pm/V) as well as good long-term stability of NLO response together with excellent chromophore thermal stability (Td = 256 °C). Composite materials doped with quinoxaline chromophores are photostable with respect to laser pulses with peak intensities up to 11 GW/cm 2 . Graphical abstract: Image 1 Highlights: Synthesis of quinoxaline-based chromophores. Structure-property of chromophores relationships. Atomistic modeling of guest-host chromophore/PMMA materials. Femtosecond nonlinear optical activity.